PROFIL PENALARAN INDUKTIF SISWA SMP DALAM MEMECAHKAN MASALAH NUMERASI PADA MATERI POLA BILANGAN - Diana Sari Hasibuan; I Nengah Parta; Abd Qohar (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Based on the results of the preliminary study, most students were unable to infer formulas of the created patterns and to apply them to the problem's context. This inability refers to inductive thinking, specifically the formulation and generalization stages.The purpose of this study is to describe the profile of students' inductive reasoning in solving numeration problems in the material of number patterns. This study uses a qualitative approach. This research was conducted at SMP Negeri 12 Malang. The stages of students' inductive reasoning are understanding the problem, organizing the problem, looking for and guessing patterns, conjecturing formulas, validating conjectures, and generalizing. The subjects in this study were three students of class VIII C SMP Negeri 12 Malang. Data collection used questions in the form of numeracy questions on number pattern material and interview guidelines. Qualitative data analysis through data reduction, data presentation, and drawing conclusions. The results of this study indicate that students with high abilities can carry out all inductive reasoning activities, students with moderate abilities carry out inductive reasoning to activities for finding and guessing patterns, and students with low abilities do not carry out inductive reasoning.